2016
DOI: 10.5513/jcea01/17.4.1836
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of basic nutritive components of venison in selected species of hoofed game

Abstract: The aim of this experiment was to obtain the differences in protein, moisture and fat content in venison (Mucsulus semimembranosus) of roe deer (Capreolus capreolus L.) and wild boar (Sus scrofa L). The monitoring of wild boar and roe deer was realized from 16 May 2016 to 16 June 2016 in red deer region JXXVIII Tribeč (Western Slovakia, Tribeč mountain). Analysis of basic nutritive components of venison were determined with FoodScan LAB Analyzer (FOSS, Denmark). The obtained average values of experimental trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Meat derived from wild animals is described as a high nutritional value product, due to the low content of fat, beneficial fatty acid composition, and favorable amino acids configuration [ 27 , 28 , 29 , 30 ]. That makes it an attractive source of proteins, considering the need to ensure high nutrition quality and current researches showing that excessive meat consumption, especially red meat, may have a negative impact on human health [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meat derived from wild animals is described as a high nutritional value product, due to the low content of fat, beneficial fatty acid composition, and favorable amino acids configuration [ 27 , 28 , 29 , 30 ]. That makes it an attractive source of proteins, considering the need to ensure high nutrition quality and current researches showing that excessive meat consumption, especially red meat, may have a negative impact on human health [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most European countries, game meat is mainly derived from red deer, roe deer, fallow deer, wild boar, wild rabbit, and wild birds of different species. A common trait characterizing wild animal meat is a number of features that have a positive impact on human health and body functioning, which is a result of its good nutrient composition (proteins, unsaturated fatty acids, vitamins, macro- and microelements) in comparison with livestock meat [ 34 , 36 , 38 , 39 ]. Though the high nutritional value of game meat has been documented, its consumption in Europe stays at a low level [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the high nutritional value provided by a rich protein content with high biological value and the beneficial composition of favorable amino acids and essential fatty acids were mentioned by several authors such as Blaska et al [ 72 ], Quaresma et al [ 73 ], Valencak et al [ 23 ], and Frunză et al [ 54 ]. Similarly, other studies found interesting associations between game meat and the concept of a healthy product due to the limited content of saturated fat [ 74 ].…”
Section: Resultsmentioning
confidence: 99%